Tingkat Stres Penderita Diabetes Mellitus Tipe 2 di Wilayah Pedesaan Selama Pandemi Covid-19 Dalam Melakukan Manajemen Perawatan Diri - Ahmad Guntur Alfianto; Miftakhul Ulfa; Mizam Ari Kurniyanti; Kurniawan Erman Wicaksono (STIKes Hang Tuah Pekanbaru, 2021)
The current condition of the COVID-19 pandemic affects health, especially for patients with type 2 diabetes mellitus in rural areas in performing self-care management. One of the impact conditions is mental health problems. The study aims were to describe the stress level of patients with type 2 diabetes mellitus in rural areas during the COVID-19 pandemic in performing self-care management. This was quantitative descriptive research with a survey approach. The sample of this study was the patients with type 2 diabetes mellitus in rural areas amounted to 149 respondents which were taken by the accidental sampling. The location of the research was carried out in three areas of Primary Health Care at Malang Regency. The measuring instrument used is the Diabetes Distress Scale (DDS). The research found the stress level of patients with type 2 diabetes mellitus were in the medium category (77.9%). The stress level based on indicators due to the emotional burden is a medium category (71.1%), due to health workers is a medium category (59.7%), due to treatment is a medium category (51%) and due to interpersonal relationships is a medium category (59.1%). Concluded that the stress level category for the patients with type 2 diabetes mellitus in rural areas during the pandemic in performing self-care management is in the medium category.